Polymer blend directed anisotropic self-assembly toward mesoporous inorganic bowls and nanosheets - Kim, Seongseop (Sci Adv, 2020)
Anisotropic mesoporous inorganic materials have attracted great interest due to their unique and intriguing properties, yet their controllable synthesis still remains a great challenge. Here, we develop a simple synthesis approach toward mesoporous inorganic bowls and two-dimensional (2D) nanosheets by combining block copolymer (BCP)–directed self-assembly with asymmetric phase migration in ternary-phase blends. The homogeneous blend solution spontaneously self-assembles to anisotropically stacked hybrids as the solvent evaporates. Two minor phases—BCP/inorganic precursor and homopolystyrene (hPS)—form closely stacked, Janus domains that are dispersed/confined in the major homopoly(methyl methacrylate) (hPMMA) matrix. hPS phases are partially covered by BCP-rich phases, where ordered mesostructures develop. With increasing the relative amount of hPS, the anisotropic shape evolves from bowls to 2D nanosheets. Benefiting from the unique bowl-like morphology, the resulting transition metal oxides show promise as high-performance anodes in potassium-ion batteries.